Chi erano gli spirituali francescani?: Indagine sul lessico identificativo di un gruppo di frati "diversamente minori" (1274-1330 ca.) - Montefusco, Antonio (Quaderni di storia religiosa medievale, 2025)
This contribution offers a comprehensive overview of the identity of the Franciscan group that historiography has called the Franciscan Spirituals, putting forward an interpretative proposal concerning the historical role of this multifaceted group, based on the self-perception that it had during the period in question. Through a systematic examination of the group’s identifying lexicon (that is, the definitions used by the group itself in internal sources), an interpretation emerges of the Spirituals' project as one of reform, that was defeated because it was uniquely hindered by the convergence of the actions of the majority of the order and the papacy.